Effect of fiber angles on hybrid fiber-reinforced polymer–concrete–steel double-skin tubular columns under monotonic axial compression. Issue 7 (May 2020) - Zhang, Bing; Zhao, Jun-Liang; Huang, Tao; Zhang, Ning-Yuan; Zhang, Yi-Jie; Hu, Xia-Min
Hybrid fiber-reinforced polymer–concrete–steel double-skin tubular columns are a novel form of hollow columns that combine two traditional construction materials (i.e. concrete and steel) with fiber-reinforced polymer composites. Hybrid fiber-reinforced polymer–concrete–steel double-skin tubular columns consist of an inner tube made of steel, an outer tube made of fiber-reinforced polymer, and a concrete layer between the two tubes. Existing studies, however, are focused on hybrid fiber-reinforced polymer–concrete–steel double-skin tubular columns with fibers of the fiber-reinforced polymer tube oriented in the hoop direction or close to the hoop direction. In order to investigate the effect of fiber angles (i.e. the fiber angle between the fiber orientation and the longitudinal axis of the fiber-reinforced polymer tube), monotonic axial compression tests were conducted on hybrid fiber-reinforced polymer–concrete–steel double-skin tubular columns with an fiber-reinforced polymer tube of ±45°, ±60°, or ±80° fiber angles. There were two types of steel tubes adopted for these hybrid fiber-reinforced polymer–concrete–steel double-skin tubular columns. The fiber-reinforced polymer tube thickness was also investigated as an important parameter. Experimental results showed that the confinement effect of the fiber-reinforced polymer tube increased with the increase of the absolute value of fiber angles, whereas the ultimate axial strain of hybrid fiber-reinforced polymer–concrete–steel double-skin tubular columns decreased with the increase of the absolute value of fiber angles. An existing stress–strain model, which was developed on the basis of hybrid fiber-reinforced polymer–concrete–steel double-skin tubular columns with an fiber-reinforced polymer tube of ±90° fiber angles, is verified using the test results of this study. For the compressive strength of the confined concrete in hybrid fiber-reinforced polymer–concrete–steel double-skin tubular columns, the existing model provides conservative predictions for specimens with a ±80° fiber-reinforced polymer tube, overestimated predictions for specimens with a ±60° fiber-reinforced polymer tube, and close predictions for specimens with a ±45° fiber-reinforced polymer tube.